Desarrollo e implementación de un sistema inteligente para el departamento de enfermería de centros de asistencia médica que permita el control de horarios para el suministro de medicamentos para pacientes internos del Hospital Militar HB-7 Loja. - Narváez Guillén, Cristian Ramiro (2012)
This final project was carried out in the hospital-I 7B Military Brigade Loja, in order to design and implement a computer system to support proper performance of everyday activities in the Department of Nursing, to support processes user management, security, backup and system access levels, medical records management, drug supply management, records management, as well as a software component based on an intelligent algorithm (Multilayer Perceptron) to the early detection of diseases defined within the period of institutional epidemiological fence in April 2011, to achieve appropriate to suggest medications symptoms presented, which after analysis of the treating physician, the recipe can generate indications and contraindications of it. The requirements gathering process and all the information required for analysis phase was performed based on investigative techniques such as surveys and interviews for managers, employees, and a significant percentage of patients and hospital information. The information was analyzed and organized with the focus provided by inductive-deductive methods and scientific, which allowed us to obtain quality information and the functional and non-functional system. For the development stage of the system is analyzed to choose from among the available technologies for application development today, and decided unilaterally to work with the Java Development Kit 6, and technologies based on it, and it is WEKA reap the benefits of a free software platform for machine learning and data mining written in Java, that in view of the stability, robustness, portability and seamless integration are the perfect choice for the development of such systems.